The transposable element profile of the anolis genome: How a lizard can provide insights into the evolution of vertebrate genome size and structure - Tollis, Marc (Landes Bioscience, 2011)
The recent sequencing of the lizard genome provides a unique opportunity to examine the evolution of vertebrate genomes in a phylogenetic context. The lizard genome contains an extraordinary diversity of active transposable elements that far exceeds the diversity reported in extant mammals and birds. Retrotransposons and DNA transposons are represented by multiple active families, contributing to the very diverse repetitive landscape of the lizard. Surprisingly, ancient transposon copies are relatively rare suggesting that the transposon copy number is tightly controlled in lizard. This bias in favor of young copies results from the joint effect of purifying selection acting on novel insertions and a high rate of DNA loss. Recent analyses have revealed that the repetitive landscape of reptiles differ drastically from other extant amniotes by their diversity but also by the dynamics of amplification of their transposons. Thus, from the point of view of mobile elements, reptile genomes show more similarity to fish and amphibians than to other amniotes.